Effects of 15% Azelaic Acid Gel in the Management of Post-Inflammatory Erythema and Post-Inflammatory Hyperpigmentation in Acne Vulgaris - Huidi Shucheng; Xinyu Zhou; Dan Du; Jiaqi Li; Chenyang Yu; Xian Jiang (Adis, Springer Healthcare, 2024)
Abstract Introduction The aim of this study was to assess the efficacy and safety of 15% azelaic acid (AzA) gel in treating acne-induced post-inflammatory erythema (PIE) and post-inflammatory hyperpigmentation (PIH). The effects of 15% AzA gel on acne, skin barrier function, and quality of life were also evaluated. Methods A total of 72 patients with mild to moderate acne were enrolled in a randomized, double-blind, placebo-controlled trial. Patients were divided into two groups: patients in the AzA group applied 15% AzA gel twice daily for 12 weeks, and those in the placebo group applied AzA-free gel. Clinical evaluations using non-invasive skin detection technologies, including VISIA skin analysis, dermoscopy, and skin physiological function tests, were performed at 0, 4, 8, and 12 weeks. Main outcome measures included the post-acne hyperpigmentation index (PAHPI), melanin, hemoglobin, individual typology angle, water content, transepidermal water loss, and sebum. Investigator Global Assessment) and Dermatology Life Quality Index (DLQI) assessments were conducted at weeks 0 and 12. Adverse reactions were recorded. Results Of the 72 patients at study initiation, 60 completed the trial. At 8 and 12 weeks, patients in the AzA group showed significantly reduced PAHPI for PIE lesions compared to baseline and patients receiving placebo (P < 0.05). Patients in both groups exhibited reduced PIH lesions at weeks 8 and 12 that differed significantly from baseline (P < 0.05). Hemoglobin content decreased significantly in AzA-treated PIE lesions compared to those treated with placebo at week 12 (P < 0.05). Melanin content decreased significantly in AzA-treated PIH lesions at week 12 (P < 0.05). The AzA group showed higher improvement in DLQI (P < 0.05), and greater overall satisfaction (P < 0.05) compared to placebo. Conclusion The results indicate that 15% AzA gel effectively improved acne-induced PIE and PIH with minimal adverse reactions, making it a viable clinical application. In the study population, it had no adverse effects on skin barrier function and contributed positively to acne improvement and patient quality of life. Trial Registration This study was registered with the Chinese Clinical Trial Registry (ChiCTR.org.cn) under the identifier ChiCTR2300076959. The registration date was 25 October 2023, retrospectively registered.